Sosialisasi Program Pendidikan Bahasa Arab Dalam Meningkatkan Minat Santri Di Pesantren Sultan Hasanuddin - Fauziah Bachtiar; Sitti Muthmainnah; Baiq Raudatussolihah; Hikmatul Laila; Dyah Adilla (CV. SINAR HOWUHOWU, 2026)
This Community Service Program (Program Pengabdian kepada Masyarakat/PKM) aims to enhance students’ interest in learning Arabic through the socialization of an Arabic language education program at Pesantren Sultan Hasanuddin. This activity is motivated by the significant potential of students to develop their Arabic language proficiency, as Arabic serves as the primary language for understanding Islamic sources as well as an international language with a strategic role in the global era. Therefore, educational efforts are needed to strengthen students’ motivation and awareness of the importance of mastering Arabic in a communicative and practical manner. The implementation method of this program consists of three stages: preparation, implementation, and evaluation. The socialization activities were carried out through material presentations, interactive discussions, as well as motivation sessions and examples of the practical use of Arabic in daily life. The results indicate an improvement in students’ understanding and interest in learning Arabic, as evidenced by their active participation during the activities and their positive responses to the program. In conclusion, the socialization of this Arabic language education program is effective in increasing students’ learning interest and can serve as an alternative strategy for developing Arabic language learning in Islamic boarding school environments.